Mapping Literature and Research Trends on AI Applications in Journalism: A Bibliometric Review - Shabrina, Masyitha Nur; Muttaqin, Nabil; Purwodani, Dio Lingga (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
An emerging field of interdisciplinary research that needs more focus is the application of AI in journalism. The bibliometric analysis of the most recent research on implementation in digital journalism is presented in this paper. From Scopus, publications from 2014 to 2023 were examined to determine subjects, performance, impact, and collaborations. The findings indicate a rise in yearly production, with over 88 publications released in 2023 attesting to heightened research activity. Additionally, more recent publications had a more significant citation effect, demonstrating their relevance today. The majority of the prolific writers are from America, China, and Spain. International collaborations are centered around the West, between the United States and China, and the United States and Korea. This offers a standard that will guide future research in this enormously promising field. For AI to be implemented in digital journalism in a responsible manner, under-represented groups must be more involved.